어머니의 양육스트레스와 영유아의 교육기관 적응의 관계 - 이자현(Ja Hyun Lee); 위영희(Yeong Hee Wui) (Korean Journal of child studies, 2012)
The purpose of this study was to analyze the relationships of mothers' parenting stress and young children's adjustment to the child care centers they attend. The subjects for this study comprised 401 young children from 1 to 4 years of age from 11 child care centers in C-si, Chungnam, and their mothers. The results of this study were as follows : First, there were no significant differences in the parenting stress of mothers related to whether they were working or not, the age of the children nor their gender Second, there were no significant differences in the adjustment of young children to their child care center related to their mothers' work status nor age of the children themselves. However, there was a significant difference in relation to the gender of the young children in that girls were better in their adjustment to the child care center than boys. Third, a negative correlation appeared between mothers' parenting stress and their young children's adjustment to the child care center in that the higher maternal parenting stress was, the greater the difficulties for their young children in their adjustment to the child care center. There were significant negatively correlations between most sub-factors of maternal parenting stress and the adjustment of those children to the child care center.